Perkembangan Motif Batik Gonggong Khas Kota Tanjungpinang (2010-2020) - Juica Prasmi Juica; Bedriati Ibrahim; Bunari Bunari (CHRONOLOGIA, 2022)
In Indonesia, batik grows and develops as a manifestation of cultural wealth in Indonesia so that there are product innovations from various regions and each region has an icon to make it easier for customers to remind batik products from each region. Batik, which originally only existed in Java, especially Central Java, then developed into other regions and each region has a variety of batik patterns that are characteristic of each region. Among other areas, the Riau Archipelago (Kepri) has batik with its distinctive style, namely marine biota such as gonggong. In this study the researchers compiled and described the development of Batik Gonggong because it was still not well known by the people and was rarely used even though it had become a typical batik from the City of Tanjungpinang. Therefore, to find out the history and development of Gonggong Batik and the government's role in preserving Gonggong Batik, this research was conducted. This study uses descriptive qualitative research methods with data collection techniques, namely through interviews, observation, documentation and literature study. From the results of the study, it was found that Efiyar A. Amin was the first to create or pioneer the Batik Gonggong motif typical of Tanjungpinang City in 2010. The government plays a role in maintaining this batik through various events held.